THE EFFECT OF CUSTOMER SATISFACTION AS A MEDIATING VARIABLE ON INSTAGRAM SOCIAL MEDIA CUSTOMER LOYALTY - Erika, Erika; Ruslim, Tommy Setiawan (International Journal of Application on Economics and Business, 2025)
Social media is like a big online club where people can talk to each other and share things with many different people around the world. One can do many different things on social media such as posting pictures and videos, playing games, and talking to friends and family. Some popular SocialMedia apps are YouTube, Facebook, Snapchat, Instagram, and Twitter. In this research, we will be talking about Instagram. Instagram itself is a specialized app where one can share pictures and videos and talk to friends and family through messages. Some people even use Instagram to sell things or promote their business online. The study aims to test and determine the variables of perceived usefulness, convenience, and security on Instagram customer loyalty in Jakarta which is mediated by customer satisfaction. The study uses non-probability sampling technique method with a purposive sampling sample type. In collecting data for this study, 212 respondents were collected which were adjusted to the characteristics in this study, namely Instagram users who are used as a means to sell and promote. The data results were tested using PLS-SEM with SmartPLS software version 4.0. It can be concluded that the test results of perceived usefulness, convenience, and security have a positive and significant influence on customer loyalty mediating by customer satisfaction.